Making the Medieval Relevant : How Medieval Studies Contribute to Improving Our Understanding of the Present. - Jones, Chris. (Das Mittelalter. Perspektiven Mediävistischer Forschung. Beihefte Series, 2019)
This new series, launched by the Medievalists' Society in 2014, provides a forum for exceptional, topically focused anthologies and conference volumes as well as medievalist monographs. The journal accepts submissions in all disciplines represented by the Society, including Byzantine studies, Latin philology, modern language philologies, history, and theology.